1991
DOI: 10.1038/353561a0
|View full text |Cite
|
Sign up to set email alerts
|

The int-2 proto-oncogene is responsible for induction of the inner ear

Abstract: The int-2 proto-oncogene encodes several products related to the fibroblast growth factor (FGF) family. FGFs have been associated with mesoderm induction in the amphibian embryo and int-2 has a distinct pattern of expression throughout development in vertebrates. But evidence for a function of int-2 in embryo-genesis has been lacking. In the mouse embryo, int-2 transcripts have been detected in the rhombencephalon at a developmental stage where classical experiments showed that the induction of the inner ear o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
93
1
3

Year Published

1995
1995
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(104 citation statements)
references
References 14 publications
7
93
1
3
Order By: Relevance
“…However, little is known to date about the molecular basis underlying these inductive and determinative processes during development of the inner ear. Embryological and genetic studies have revealed important roles for FGF-3 during induction and/or compartimentalization of the inner ear (Represa et al, 1991;Mansour et al, 1993). FGF-3 is expressed in the hindbrain and otic vesicle during its patterning and differentiation (Wilkinson et al, 1989) and also FGF-2 is expressed by the otic vesicle (Dono and Zeller, unpublished data).…”
Section: Discussion Ld Proteins and Establishment Of The Vestibular Amentioning
confidence: 99%
“…However, little is known to date about the molecular basis underlying these inductive and determinative processes during development of the inner ear. Embryological and genetic studies have revealed important roles for FGF-3 during induction and/or compartimentalization of the inner ear (Represa et al, 1991;Mansour et al, 1993). FGF-3 is expressed in the hindbrain and otic vesicle during its patterning and differentiation (Wilkinson et al, 1989) and also FGF-2 is expressed by the otic vesicle (Dono and Zeller, unpublished data).…”
Section: Discussion Ld Proteins and Establishment Of The Vestibular Amentioning
confidence: 99%
“…It has become clear that FGF-derived signals constitute a significant part of this inductive capacity (Represa et al, 1991;Ladher et al, 2000;Vendrell et al, 2000;Phillips et al, 2001;Leger and Brand, 2002;Maroon et al, 2002;Liu et al, 2003). In zebrafish, fgf3/8 are expressed in mesendoderm and hindbrain and appear to function as inductive signals at multiple points during otic placode development Phillips et al, 2001;Leger and Brand, 2002;Maroon et al, 2002;Liu et al, 2003).…”
Section: Requirement For Foxi1 In Fgf3/8 Induction Of the Otic Placodementioning
confidence: 99%
“…Fibroblast growth factor (FGF) molecules have been identified as inductive signals for otic placode development in several vertebrate species (Represa et al, 1991;Mansour et al, 1993;De Moerlooze et al, 2000;Ohuchi et al, 2000;Pirvola et al, 2000Pirvola et al, , 2002Vendrell et al, 2000;Phillips et al, 2001;Leger and Brand, 2002;Maroon et al, 2002). Depletion of FGF3 prevents otic vesicle formation in tissue explants from chick (Represa et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be caused by the lack of antigen preservation, by nonspecific staining reaction, or by other mechanisms not fully understood, leading to negative immunohistochemical staining result. In the mouse, fgf4 and int2 are known to be expressed during embryogenesis (22,23). Assuming the expression pattern to be similar in humans, no expression would be expected in normal adult tissues.…”
Section: Discussionmentioning
confidence: 99%